1991
DOI: 10.1099/0022-1317-72-6-1269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mutations in glycosylation sites and disulphide bonds on processing, CD4-binding and fusion activity of human immunodeficiency virus envelope glycoproteins

Abstract: Site-directed mutagenesis was used to study the biological significance of a disulphide bridge and two N-linked oligosaccharides in the CD4-binding region of the envelope glycoproteins of human immunodeficiency virus type 1. Mutagenesis was performed in a phage M13 system at sites corresponding to the cysteine residue (amino acid 402) and the asparagine residues (390 and 447) of the env gene. The mutated env gene was inserted into a recombinant vaccinia virus under the control of the vaccinia virus 7.5K promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Bolmstedt et al (27) reported that the removal of N-linked glycosylation sites represented by our mutants 406 and 463 from the envelope recombinant proteins expressed by a vaccinia expression vector did not affect CD4 receptor binding or syncytium formation (27). Their results are compatible with our finding that CD4-positive SupT1 cells were readily infected by our mutants 406 and 463, and support our hypothesis that the N-linked glycosylation sites located in the carboxyl-terminal half ofgp120 are more dispensable for viral infectivity than those located in the amino-terminal half.…”
Section: Discussionmentioning
confidence: 99%
“…Bolmstedt et al (27) reported that the removal of N-linked glycosylation sites represented by our mutants 406 and 463 from the envelope recombinant proteins expressed by a vaccinia expression vector did not affect CD4 receptor binding or syncytium formation (27). Their results are compatible with our finding that CD4-positive SupT1 cells were readily infected by our mutants 406 and 463, and support our hypothesis that the N-linked glycosylation sites located in the carboxyl-terminal half ofgp120 are more dispensable for viral infectivity than those located in the amino-terminal half.…”
Section: Discussionmentioning
confidence: 99%
“…First, patient sera were assayed for their ability to block binding between gp 120 and cell-associated CD4 in a kinetic assay (B. Svennerholm, unpublished results), gpl20, purified from green monkey kidney cells infected with a gpl20-encoding recombinant virus (Bolmstedt et al, 1991), was allowed to bind to CD4 ÷ HeLa cells with or without preincubation with dilutions of serum for 15 rain at 37 °C. The amount of gpl20 adsorbed to the cell surface was measured directly in an ELISA system using the anti-V3 (IIIB) MAb F58/H3 as detecting antibody (negative control CD4-HeLa cells).…”
Section: Cd4-binding Inhibition Assaymentioning
confidence: 99%
“…However, once fully glycosylated proteins have been produced, these carbohydrate moieties do not appear to be required to maintain native protein structure, since enzymatically deglycosylated core envelope proteins retain their ability to bind CD4 and many conformationally dependent antibodies (28)(29)(30). In addition, despite the general requirement for carbohydrates in the production of envelope proteins, it is possible to remove some individual sites without impairing the ability of these glycosylation mutant envelope proteins to bind CD4 or yield replication-competent viruses (3,4,26). For years, it has been suggested that these carbohydrates serve as a barrier to shield the virus from effective immune recognition and control.…”
mentioning
confidence: 99%